Sustainable gardens: a resource for environmental education in municipal public schools in Caxias-MA, Brazil (Research, Society and Development, 2022)
The practices of Environmental Education appear in the current context as a solution to the current environmental imbalance, being applied in an interdisciplinary way. In this sense, the school is the ideal place to apply environmental education practices, due to the possibility of working in a didactic and transversal way. Thus, the objective of this work was to develop intervention actions in an elementary school in the city of Caxias-MA, through the construction of a sustainable garden, providing knowledge about themes involving the Environment and Environmental Education. The work was developed in an elementary school. Initially, a lecture on Environmental Education was prepared and the project was presented to the students. Then the students went to visit the seedling production site located at CESC-UEMA, to know and learn about the process of cultivation and care for the plants. The following steps were the preparation of recyclable materials and later the planting of seedlings. The last stage of this work was the elaboration and recording of a lecture to present to other schools in the municipality. Thus, the importance of working on Environmental Education inside and outside the school became clear, putting into practice concepts of Environmental Education, and cultivating values for a more harmonious coexistence with the environment.